2013
DOI: 10.1186/1472-6882-13-371
|View full text |Cite
|
Sign up to set email alerts
|

Studies on two polyherbal formulations (ZPTO and ZTO) for comparison of their antidyslipidemic, antihypertensive and endothelial modulating activities

Abstract: BackgroundCardiovascular disorders (CVDs) are the leading cause of disease burden worldwide. Apart from available synthetic drugs used in CVDs, there are many herbal formulations including POL-10 (containing 10 herbs), which have been shown to be effective in animal studies but POL-10 was found to cause tachycardia in rodents as its side effect. This study was designed to modify the composition of POL-10 for better efficacy and/or safety profile in CVDs.MethodsTo assess the antidyslipidemic, antihypertensive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…On the other hand, treatment with black pepper, coffee, and their mixture improve the serum glucose, insulin, and insulin resistance (Table 1), these results agree with Rezq and Fathy and Aziz et al [20,41], who suggested that black pepper and coffee decreased glucose and insulin and may reduce risk of type 2 diabetes as they decrease the oxidative stress. Furthermore, coffee improves blood glucose level and glucose homeostasis which may be due to the inhibition of adenosine receptors that activate cyclic AMP-dependent protein kinase [51].…”
supporting
confidence: 82%
See 1 more Smart Citation
“…On the other hand, treatment with black pepper, coffee, and their mixture improve the serum glucose, insulin, and insulin resistance (Table 1), these results agree with Rezq and Fathy and Aziz et al [20,41], who suggested that black pepper and coffee decreased glucose and insulin and may reduce risk of type 2 diabetes as they decrease the oxidative stress. Furthermore, coffee improves blood glucose level and glucose homeostasis which may be due to the inhibition of adenosine receptors that activate cyclic AMP-dependent protein kinase [51].…”
supporting
confidence: 82%
“…This may be due to triton WR-1339 is known to induce hyperlipidemia in two phases: Phase I in which there is an increased hepatic cholesterol biosynthesis through triton's interference with the tissue uptake of plasma lipids, whereas Phase II involves triton's interference with cholesterol excretion and metabolism [41], in the same line, in HFD models, hyperlipidemia is induced when dietary lipid including cholesterol inhibits FA oxidation and LDL cholesterol uptake [4].…”
Section: Resultsmentioning
confidence: 94%
“…The relative safety of natural products when used for longer duration might be because of the presence of synergistic and/or side effects neutralizing constituents inbuilt in medicinal herbs [ 11 ]. In our settings due to cultural acceptance, people prefer to use herbal remedies for the treatment of various chronic ailments like gastro-intestinal [ 12 ], respiratory tract [ 13 ], endocrine (diabetes) [ 14 ] and cardiovascular disorders [ 15 ]. Despite using individual herbs to treat different ailments, there are multiple evidences supporting therapeutic use of compound formulations in the treatment of hypertension and dyslipidemia.…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted by Saravanan et al, (2007) in hypercholesterolemic rats, Belericae fructus preparations can reduce total cholesterol, LDL-C, and triglyceride levels at a dose 1 g/kgBW. Other studies on animal models also showed similar results (Aziz et al, 2013;Shaila et al, 1998). Mechanism of action of Belericae fructus is thought to inhibit lipid biosynthesis and reduce the absorption of cholesterol in the intestine.…”
Section: Resultsmentioning
confidence: 55%